Application of сolored decorative coatings on structural steels surface - Semen M. Lipkin; Svetlana V. Kucherenko; Irina Y. Zhukova; Maria V. Kolchina (Advanced Engineering Research)
Introduction. Chemical decorative treatment of steel consists in painting steel products and applying oxide films to the surface to create an attractive appearance and prevent the product from rust. Staining copper organic compounds with aqueous solutions has the following feature: the coating color varies depending on the resistance time in solution, which is associated with changing in thickness of the forming oxide layer where interference phenomena occur. For a wide application of this method, studies are needed to investigate the relationship between the staining modes and the resulting coating color. The work objective is to establish relationship between the coating staining obtained from alkaline copper-containing solutions and their quantitative and qualitative phase composition. Materials and Methods. The phase composition of the coatings obtained was studied by the method of local electrochemical analysis (LEA) based on the cathodic reduction of the oxide phases of the coatings in the galvanopulse mode using a clamp sensor. From the obtained impulse chronopotentiograms, the potential values at the pause moment were considered, and then these values were compared to the standard potentials of various redox pairs of copper oxides. Research Results. The analyzed coatings were formed during different time of holding the sample in solution and had a different color. The data of the redox pair correspond to: [[Сu(OH)4]2-/Cu - adsorption layer of hydroxocuprate-anions on the surface of electrodeposited copper steel; Cu(OH)2/Cu - adsorption layer of copper hydroxide on the surface of electrodeposited copper; Cu2О/Cu - oxide film of copper oxide (I) on copper. This equates to conclude about the colored coatings composition on the samples studied. Brown, violet and blue films formed during the initial period of exposure of the copper coating in solution contain adsorbed hydroxocuprate and copper hydroxide. Blue, yellow and lilac films formed over a longer period of time contain, in addition to these phases, copper oxide (I). Discussion and Conclusions. From the data obtained, it follows that the management of the color change time required in various technological applications can be carried out through changing the concentration of copper sulfate, as well as an organic reducing agent. The mechanism of coating coloration is affected by the adsorption layers formed on the steel surface. By varying the aging time of the sample in the electrolyte, it is possible to control the phase composition of the adsorption layers, and, consequently, influence the coating colorability.